Nanoparticles With Affinity for α-Synuclein Sequester α-Synuclein to Form Toxic Aggregates in Neurons With Endolysosomal Impairment - Jiang, Peizhou; Gan, Ming; Yen, Shu-Hui; Dickson, Dennis W. (Frontiers in Molecular Neuroscience, 2021)
Parkinson's disease (PD) is one of the most common neurodegenerative diseases. It is characterized pathologically by aggregation of α-synuclein (αS) in the form of Lewy bodies and Lewy neurites. A major challenge in PD therapy is poor efficiency of drug delivery to the brain due to the blood brain barrier. For this reason, nanomaterials, with significant advantages in drug delivery, have gained attention. On the other hand, recent studies have shown that nanoparticles can promote αS aggregation in salt solution. Therefore, we tested if nanoparticles could have the same effect in cell models. We found that nanoparticle can induce cells to form αS inclusions as shown in immunocytochemistry, and detergent-resistant αS aggregates as shown in biochemical analysis; and nanoparticles of smaller size can induce more αS inclusions. Moreover, the induction of αS inclusions is in part dependent on endo-lysosomal impairment and the affinity of αS to nanoparticles. More importantly, we found that the abnormally high level of endogenous lysosomotropic biomolecules (e.g. sphingosine), due to impairing the integrity of endo-lysosomes, could be a determinant factor for the susceptibility of cells to nanoparticle-induced αS aggregation; and deletion of GBA1 gene to increase the level of intracellular sphingosine can render cultured cells more susceptible to the formation of αS inclusions in response to nanoparticle treatment. Ultrastructural examination of nanoparticle-treated cells revealed that the induced inclusions contained αS-immunopositive membranous structures, which were also observed in inclusions seeded by αS fibrils. These results suggest caution in use of nanoparticles in PD therapy. Moreover, this study further supports the role of endo-lysosomal impairment in PD pathogenesis, and suggests a possible mechanism underlying formation of membrane-associated αS pathology.